2009
DOI: 10.1128/iai.00788-08
|View full text |Cite
|
Sign up to set email alerts
|

Sequential B-Cell Epitopes ofBacillus anthracisLethal Factor Bind Lethal Toxin-Neutralizing Antibodies

Abstract: The bipartite anthrax lethal toxin (LeTx) consisting of protective antigen (PA) and lethal factor (LF) is a major virulence factor contributing to death from systemic Bacillus anthracis infection. The current vaccine elicits antibodies directed primarily to PA; however, in experimental settings serologic responses to LF can neutralize LeTx and contribute to protection against infection. The goals of the present study were to identify sequential B-cell epitopes of LF and to determine the capacity of these deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 57 publications
0
44
0
Order By: Relevance
“…29 Previous attempts have shown, for example, that neutralizing polyclonal 41 and monoclonal 42,43 antibodies are protective against edema toxin challenge, and suggest a modest benefit in vivo during murine infection with the Sterne strain. 43 Clearly, the guinea pig model will help reassess the role of ET during infection.…”
Section: Discussionmentioning
confidence: 99%
“…29 Previous attempts have shown, for example, that neutralizing polyclonal 41 and monoclonal 42,43 antibodies are protective against edema toxin challenge, and suggest a modest benefit in vivo during murine infection with the Sterne strain. 43 Clearly, the guinea pig model will help reassess the role of ET during infection.…”
Section: Discussionmentioning
confidence: 99%
“…From a total of 384 cloned hybridomas that were screened by this method, 39 (ϳ10%) produced MAbs that reacted with PA 83 . Six of these recognized PA 32 , suggesting that they were specific for domain 3 or 4. These six MAbs were further subjected to a peptide array ELISA consisting of 12-aa peptides with 4-aa overlaps, spanning domains 3 and 4 of PA 83 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We produced a collection of B-cell hybridomas from the spleens of BALB/c mice immunized with an adjuvanted derivative of rPA (see Materials and Methods). Hybridoma supernatants were screened simultaneously by ELISA for reactivity with PA 83 and PA 32 . PA 32 is a recombinant protein consisting only of PA domains 3 and 4 (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies have shown that immunization with a DNA construct encoding the N-terminal fragment of EF elicited protective immunity against a subcutaneous challenge of A/J mice with the B. anthracis Sterne strain (38). Moreover, our studies have demonstrated that immunization with recombinant LF (rLF) can induce high-titer protective antibodies in vivo and in vitro (28).…”
mentioning
confidence: 90%